SIMULATION MODEL FOT POST-MINING PIT LAKE INFILLING AT PT XYZ'S MINING PIT - Syahrani, Mega
PT XYZ is a copper and gold mining company in Indonesia that will begin postmining activities in 2030. Currently, the company is facing challenges in planning the filling of the mine pit, which is estimated to hold 1,383,703,158 m³ of water at the spillway elevation of 260 mRL. The company’s target is to reach the spillway level as quickly as possible, while ensuring the water quality meets environmental standards. Therefore, a simulation of the pit lake filling process is needed to determine the time required for filling. This research aims to simulate the filling process by engineering a rapid filling method that also considers the variability of rainfall. The simulation is based on a water balance equation modeled using the GoldSim software. The filling simulation begins with an analysis of the input and output components during the filling process. Monthly rainfall and evaporation data from 2002-2022 are subjected to a distribution fitting test, followed by the application of the cumulative distribution function method. Monthly planned rainfall and evaporation values are derived using various probability values, representing pessimistic, optimistic, and most likely conditions for the filling plan. A topographic analysis is conducted to determine the area and runoff coefficient of the catchment area. The pit geometry is also analyzed to determine the relationship between the rise in water surface elevation and the volume and surface area of the water body, as well as the groundwater outflow. All data used are secondary data obtained from PT XYZ and previous research. The simulation is performed using three accelerated filling scenarios with surface runoff augmentation: Baseline Scenario, With Jungle, and With Jungle and Pumping. The total annual rainfall used is 1,673.271 mm, 2,652.37 mm, and 3,298.47 mm, representing rainfall probabilities of P25%, P60%, and P75%, corresponding to each condition. The planned evaporation value is 950.8 mm per year. The total catchment area for each filling scenario is 1,245.3 Ha, 1,823.8 Ha, and 2,503.38 Ha, which are further divided based on their characteristics. The simulation results show that the filling time ranges between 22.4 to 47.9 years after mining ceases, depending on the scenario and rainfall probability used. It was found that the With Jungle and Pumping Scenario is the most effective in achieving the company’s goal of accelerating the filling of the post-mining pit at PT XYZ.